Preliminary Clinical Experience of trans-1-Amino-3-(18)F-fluorocyclobutanecarboxylic Acid (anti-(18)F-FACBC) PET/CT Imaging in Prostate Cancer Patients - Kairemo, Kalevi (Hindawi Publishing Corporation, 2014)
Background. In this retrospective analysis we assessed the role of [(18)F]-FACBC-PET/CT in the prostatic cancer staging. Procedure. 30 first [(18)F]-FACBC-PET/CT images of 26 patients (68.1 ± 5.8 years) were analyzed. PET/CT findings were compared with PSA concentrations, with PSA doubling times (PDT), and with correlative imaging. Results. On 16 [(18)F]-FACBC (53.3%) scans, 58 metabolically active lesions were found. 12 (20.7%) lesions corresponding to the local relapse were found in prostate/prostate bed and seminal vesicles, 9 (15.5%) lesions were located in regional lymph nodes, 10 (17.2%) were located in distal lymph nodes, and 26 (44.8%) metabolically active lesions were found in the skeleton. In one case, focal uptake was found in the brain, confirmed further on MRI as meningioma. The mean S-PSA level in patients with positive [(18)F]-FACBC findings was 9.5 ± 16.9 μg/L (0.54–69 μg/L) and in patients with negative [(18)F]-FACBC findings was 1.96 ± 1.87 μg/L (0.11–5.9 μg/L), but the difference was not statistically significant. However, the PSA doubling time (PDT) in patients with positive findings was significantly shorter than PDT in patients with negative findings: 3.25 ± 2.09 months (0.3–6 months) versus 31.2 ± 22.02 months (8–84 months), P < 0.0001. There was a strong positive correlation between PSA value and number of metabolically active lesions (R = 0.74) and a negative correlation between PDT and number of metabolically active lesions (R = −0.56). There was a weak negative correlation between PDT and SUV(max⁡) (R = −0.30). Conclusion. According to our preliminary clinical experience, [(18)F]-FACBC-PET may play a role in in vivo restaging of an active prostate cancer, especially in patients with a short S-PSA doubling time.